Expression analysis of two SOMATIC EMBRYOGENESIS RECEPTOR KINASE (SERK) genes during in vitro morphogenesis in Spanish cedar (Cedrela odorata L.) - Porras Murrillo, Romano (2018)
Somatic embryogenesis (SE) is one of the most important steps during regeneration, but the molecular mechanism of SE remains unclear for Cedrela odorata. SOMATIC EMBRYOGENESIS RECEPTOR-LIKE KINASE (SERK) is one of the genes associated with induction of SE and is considered a marker of cells competent to form somatic embryos. Our objective was to clone and characterize the SERK1 and SERK2 gene homologues and analyze their expression patterns during in vitro morphogenesis in Spanish cedar. CoSERK1 and CoSERK2 were isolated from cedar, both share domains characteristic of the SERK family, including leucine-rich repeats, a proline-rich motif, a transmembrane domain, and kinase domains. Embryo- genic cultures were established from callus cultures induced on medium supplemented with 1 mg/L dicamba. Histological sections were studied to determine the embryogenic nature of the samples. The CoSERK1 gene was highly expressed dur- ing the acquisition of embryogenic competence. The expression level of SERK1 was lower in non-embryogenic tissues and organs than in embryogenic calli, and it was higher in 3-week old embryogenic calli. CoSERK2 gene was highly expressed in leaves and shoots but no dierence in expression was obtained between somatic and embryogenic tissues. These results suggest that the expression of CoSERK1 is associated with somatic embryogenesis induction and could be used as a potential marker to monitor the transition from competent to embryogenic cells and tissues in Spanish cedar.